Surface modification, characterization and properties of regenerated cellulose NYPA fructicans filled microcrystalline cellulose biocomposite films - Vaniespree, Govindan (Universiti Malaysia Perlis (UniMAP), 2017)
Doctor of Philosophy in Materials Engineering. Confidential item (contains confidential information under the Official Secret Act 1972*)